Akses Informasi Pemustaka Tunanetra Pada Layanan Braille Corner Di Dinas Kearsipan Dan Perpustakaan Kota Jambi - Putri, Oktaviani Dwi; Rum, Muhammad (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
Introduction. This research is entitled Information Seeker Behavior of Blind Users in Braille Corner Services at the Jambi City Archives and Libraries Service, the purpose of this study is to determine the behavior of the blind in seeking information at the Jambi City Archives and Library Service. Information seeking behavior arises because of the need for information, so the higher the need for information, the higher the number of activities seeking information. Information behavior by users has its own pattern. Because each user will find the information they need differently, therefore the need for information is very important. From this difference, the writer is interested in studying "The Behavior of Information Seekers for the Braille Corner Service for Blind Users at the Jambi City Archives and Library Service". Data Collection Method. This study uses a qualitative descriptive method in the form of case study research. Informants in researching 3 people, informants were selected based on purposive sampling. Data collection techniques in this study were observation, in-depth interviews and documentation, the subjects in this study were blind users who visited the Braille Corner service. Data Analysis. Data analysis techniques in this study used data reduction, data presentation and drawing conclusions. Result and Discusions. The results obtained from the search for information on Braille Corner services for blind users at the Jambi City Archives and Library Service are strongly influenced by Braille Corner service officers. The type of information that is often accessed by blind users at the Jambi City Archives and Library Service is the printed collection of Braille. Information obtained by blind users is used for their respective interests and is used for different purposes.